Regenerative potential of leucocyte‐ and platelet‐rich fibrin. Part B: sinus floor elevation, alveolar ridge preservation and implant therapy. A systematic review. (10th January 2017) - Castro, Ana B.; Meschi, Nastaran; Temmerman, Andy; Pinto, Nelson; Lambrechts, Paul; Teughels, Wim; Quirynen, Marc
Abstract: Aim: To analyse the effect of leucocyte‐ and platelet‐rich fibrin (L‐PRF) on bone regeneration procedures and osseointegration. Materials and Methods: An electronic and hand search was conducted in three databases (MEDLINE, EMBASE and Cochrane). Only randomized clinical trials, written in English where L‐PRF was applied in bone regeneration and implant procedures, were selected. No follow‐up restrictions were applied. Results: A total of 14 articles were included and processed. Three subgroups were created depending on the application: sinus floor elevation (SFE), alveolar ridge preservation and implant therapy. In SFE, for a lateral window as well as for the trans‐alveolar technique, histologically faster bone healing was reported when L‐PRF was added to most common xenografts. L‐PRF alone improved the preservation of the alveolar width, resulting in less buccal bone resorption compared to natural healing. In implant therapy, better implant stability over time and less marginal bone loss were observed when L‐PRF was applied. Meta‐analyses could not be performed due to the heterogeneity of the data. Conclusions: Despite the lack of strong evidence found in this systematic review, L‐PRF might have a positive effect on bone regeneration and osseointegration.